The Proinflammatory and Proangiogenic Macrophage Migration Inhibitory Factor Is a Potential Regulator in Proliferative Diabetic Retinopathy - Abu El-Asrar, Ahmed M.; Ahmad, Ajmal; Siddiquei, Mohammad Mairaj; De Zutter, Alexandra; Allegaert, Eef; Gikandi, Priscilla W.; De Hertogh, Gert; Van Damme, Jo; Opdenakker, Ghislain; Struyf, Sofie (Frontiers in Immunology, 2019)
The macrophage migration inhibitory factor (MIF)/CD74 signaling pathway is strongly implicated in inflammation and angiogenesis. We investigated the expression of MIF and its receptor CD74 in proliferative diabetic retinopathy (PDR) to reveal a possible role of this pathway in the pathogenesis of PDR. Levels of MIF, soluble (s)CD74, soluble intercellular adhesion molecule-1 (sICAM-1) and vascular endothelial growth factor (VEGF) were significantly increased in the vitreous from patients with PDR compared to nondiabetic control samples. We detected significant positive correlations between the levels of MIF and the levels of sICAM-1 (r=0.43; p=0.001) and VEGF (r=0.7; p<0.001). Through immunohistochemical analysis of PDR epiretinal membranes, significant positive correlations were also found between microvessel density (CD31 expression) and the numbers of blood vessels expressing MIF (r=0.56; p=0.045) and stromal cells expressing MIF (r=0.79; p=0.001) and CD74 (r=0.59; p=0.045). Similar to VEGF, MIF was induced in cultured Müller cells under hypoxic conditions and MIF induced phosphorylation of ERK1/2 and VEGF production in those cells. Intravitreal administration of MIF in normal rats induced increased retinal vascular permeability and significant upregulation of phospho-ERK1/2, NF-κB, ICAM-1 and vascular cell adhesion molecule-1expression in the retina. MIF induced migration and proliferation of human retinal microvascular endothelial cells. These results suggest that MIF/CD74 signaling is involved in PDR angiogenesis.